A new photo switchable azobenzene macrocycle without thermal relaxation at ambient temperature. Issue 1 (21st December 2020) - Eleya, Nadi; Ghosh, Souvik; Lork, Enno; Staubitz, Anne
Abstract : An azobenzene macrocycle shows no thermal relaxation of Z -isomer at 25 °C, although photochemical switching is facile. Abstract : A new switchable azobenzene macrocyclic derivative has been prepared in 4 steps with an overall yield of 47%. This molecule shows photoisomerization between the E and Z isomers using light of 365 nm and 405 nm respectively. What differentiates this macrocyclic switch from azobenzene is that the λ max for E (ππ*) and Z (nπ*) are well separated by 99 nm. The photostationary state (PSS) after irradiating by 365 nm LED light (measured at 415 nm) had a Z -selectivity of 81% Z and the PSS after irradiating by 405 nm LED light (measured at 316 nm) had an E -selectivity of 88% E . Both were reached after 90 s. The most unusual feature was that there was no thermal relaxation from Z to E observed at 20 °C over a period of 120 days, although photo switching was facile. Even at elevated temperatures of 70 °C and 90 °C, the thermal half-lives of the Z -isomer were as high as 36.4 hours and 2.35 hours respectively. Unusually, the macrocycle does not only photoisomerize in solution but also in the solid state. Therefore, this macrocycle could be useful for data storage and solar fuels applications.